Spontaneous Intracranial Hypotension - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the Department of Neurosurgery, Cedars-Sinai Medical Center, Los Angeles, CA, evaluated 24 children (18 girls, 6 boys) with spontaneous intracranial hypotension, seen 2001-2012.